Testing the Complete Plastome for Species Discrimination, Cryptic Species Discovery and Phylogenetic Resolution in Cephalotaxus (Cephalotaxaceae) - Wang, Jie; Fu, Chao-Nan; Mo, Zhi-Qiong; Möller, Michael; Yang, Jun-Bo; Zhang, Zhi-Rong; Li, De-Zhu; Gao, Lian-Ming (Frontiers in Plant Science, 2022)
Species of Cephalotaxus have great economic and ecological values. However, the taxonomy and interspecific phylogenetic relationships within the genus have been controversial and remained not fully resolved until now. To date, no study examined the efficiency of the complete plastome as super-barcode across Cephalotaxus species with multiple samples per taxon. In this study, we have evaluated the complete plastome in species discrimination and phylogenetic resolution in Cephalotaxus by including 32 individuals of all eight recognized species and five varieties following Farjon’s classification (2010) with multiple samples per taxon. Our results indicated that not all species recognized in recent taxonomic revisions of Cephalotaxus could be distinguished and not all were monophyletic. Based on the plastome phylogeny, a new taxonomic classification for the genus comprising nine species and two varieties, including a cryptic species, was proposed. The phylogeny also resolved all interspecific relationships. Compared to the plastome based classification, standard DNA barcodes, alone or in combination, only recognized a maximum of seven out of the nine species. Moreover, two highly variable single loci, ycf1 and rps16, each alone achieved full species discrimination. With the moderate length of 1079 bp, rps16 is proposed as a specific barcode to discriminate Cephalotaxus species. The super-barcodes and specific barcode candidates will aid in the identification of endangered Cephalotaxus species, and to help focus conservation measures.